The Role of ChatGPT as an AI-Assisted Learning Tool in Teaching Arabic to Students at Higher Education Institution Malang - Fredlina, Sipta Firstina; Ismail, Zakia Maryam Raihana; Khusnah, Emma Ummiyatul; Hilmi, Danial (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3809, 2025)
This study explores students perceptions of the role, obstacles, and impact of ChatGPT in Arabic language learning at three religious universities in Malang City. The method used is quantitative descriptive, involving 152 seventh-semester students from the Arabic Language Education program who have been using ChatGPT for at least six months. Data were obtained through a questionnaire with a 1-5 Likert scale and analyzed statistically using a descriptive approach. The research findings show that ChatGPT is very useful for receptive skills with achievements such as simplifying reading (75%), translating writing (66.5%), and expanding vocabulary (61.8%). However, its effectiveness was lacking in productive skills such as corrected writing (32.2%) and speaking practice (42.7%). The main obstacles encountered included inaccuracies in Arabic grammar (63.8%), limitations in audio and visual features (63.2%), and confusion about plagiarism (60.6%). In addition, difficulties in designing effective prompts (40.7%) and concerns about accusations of cheating (55.3%) are also significant obstacles. The impact of ChatGPT shows that this tool is considered useful (58.6%) and can accelerate understanding (50%), although its effect on overall understanding is moderate (39.5%). This study concludes that ChatGPT has great potential if supported by ethical policies, digital literacy training, and humanistic blended learning models.